STUDENTS’ PERCEPTION ON THE EFFECT OF ONLINE LEARNING DURING COVID 19 - Dawi Yanti (Universitas Muhammadiyah Kalimantan Timur, 2021)
The educational system across the world has been affected due to outbreak of Covid-19 pandemic, this new phenomenon forced teachers and students to do teaching and learning process from home. The purpose of writing this study was to investigate the students' perceptions of online learning has been implemented and the factors that influenced these perceptions. Therefore, this survey asked 60 students in Sekolah Tinggi Teknologi Migas Balikpapan to convey their perception on the effect of online during Covid-19. The finding of this study revealed that students positively accepted this new learning system although they’ve found some problems such as difficulty in using application and lack of the internet connection, etc.